Evaluation of carotid intima-media thickness and factors associated with cardiovascular disease in children and adolescents with chronic kidney disease - Renata Lopes; Mauro Batista de Morais; Fernanda Luisa Ceragioli Oliveira; Ana Paula Brecheret; Ana Lucia Cardoso Santos Abreu; Maria Cristina de Andrade (Elsevier, 2019)
Objective: To assess the carotid intima-media thickness and factors associated with cardiovascular disease in children and adolescents with chronic kidney disease. Material and methods: Observational, cross-sectional study carried out at the Universidade Federal de São Paulo (chronic kidney disease outpatient clinics) with 55 patients (60% males) with a median age of 11.9 years (I25-I75: 9.2-14.8 years). Of the 55 patients, 43 were on conservative treatment and 12 were on dialysis. Serum laboratory parameters (creatinine, uric acid, C-reactive protein, total cholesterol and fractions, and triglycerides), nutritional status (z-score of body mass index, z-score of height/age), body fat (fat percentage and waist circumference), and blood pressure levels were evaluated. The carotid intima-media thickness measure was evaluated by a single ultrasonographer and compared with percentiles established according to gender and height. Data collection was performed between May 2015 and March 2016. Results: Of the children and adolescents with chronic kidney disease, 74.5% (95% CI: 61.0; 85.3) showed an increase (>P95) in carotid intima-media thickness. In patients with stages I and II hypertension, 90.9% had increased carotid intima-media thickness. Nutritional status, body fat and laboratory tests were not associated with increased carotid intima-media thickness. After multivariate adjustment, only puberty (PR = 1.30, p = 0.037) and stages I and II arterial hypertension (PR = 1.42, p = 0.011) were independently associated with carotid intima-media thickness alterations. Conclusion: The prevalence of increased carotid thickness was high in children and adolescents with chronic kidney disease. Puberty and arterial hypertension were independently associated with increased carotid intima-media thickness. Resumo: Objetivo: Avaliar a espessura médio-intimal da carótida e os fatores associados à doença cardiovascular em crianças e adolescentes com doença renal crônica. Material e métodos: Estudo observacional transversal feito na Universidade Federal de São Paulo (ambulatórios de doença renal crônica) com 55 pacientes (60% do sexo masculino) com mediana de 11,9 anos (I25-I75: 9,2-14,8). Dos 55 pacientes, 43 estavam em tratamento conservador e 12 em terapia dialítica. Foram avaliados os parâmetros laboratoriais séricos (creatinina, ácido úrico, proteína C-reativa, colesterol total e frações e triglicérides), estado nutricional (escore z de índice de massa corpórea, escore z de estatura/idade), gordura corporal (percentual de gordura e circunferência abdominal) e pressão arterial. A medida da espessura médio-intimal da carótida foi avaliada por um único ultrassonografista e comparada com percentis estabelecidos de acordo com o sexo e a estatura. A coleta de dados foi feita entre maio de 2015 e março de 2016. Resultados: Das crianças e adolescentes com doença renal crônica, 74,5% (IC 95%: 61,0; 85,3) apresentaram aumento (> P95) da espessura médio-intimal da carótida. Nos pacientes com hipertensão arterial estágios I e II, 90,9% apresentaram aumento da espessura médio-intimal da carótida. O estado nutricional, a gordura corporal e os exames laboratoriais não apresentaram associação com o aumento da espessura médio-intimal da carótida. Após ajuste multivariado, apenas a puberdade (RP = 1,30; p = 0,037) e a hipertensão arterial estágios I e II (RP = 1,42; p = 0,011) mostraram-se independentemente associados à alteração da espessura médio-intimal da carótida. Conclusão: A prevalência do aumento da espessura da carótida foi elevada em crianças e adolescentes com doença renal crônica. A puberdade e a hipertensão arterial mostraram-se independentemente associadas ao aumento da espessura médio-intimal da carótida. Keywords: Chronic kidney disease, Cardiovascular diseases, Carotid intima-media thickness, Adolescents, Children, Palavras-chave: Insuficiência renal crônica, Doenças cardiovasculares, Espessura intima-média carotídea, Adolescentes, Crianças